Pengaruh Distrupsi Digitalisasi Terhadap Preferensi Konsumen: Studi Kasus pada Mahasiswa Tazkia di Pasar Dramaga - Syauqi Imam Ahmadi; Sebastian Herman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to analyze the influence of digital disruption on consumer preferences in product or service selection. This study utilizes the Structural Equation Modeling Partial Least Square (SEM-PLS) model. The results indicate that digital disruption significantly affects consumer preferences. Changes in consumer behavior triggered by digital advancements, such as the ease of shopping through online platforms, are crucial factors influencing consumer preferences. However, in this context, the influence of price on consumer preferences is not significant. Although important, price is not the primary factor in purchasing decisions, as other factors such as product quality, service, and halal labeling have a greater influence. Halal certification is also an important consideration for consumers, as it reflects values of halalness and cleanliness that are deemed important. This study provides valuable insights for businesses in understanding the impact of digital disruption on consumer behavior and implementing appropriate marketing strategies to enhance consumer preferences.